2009
DOI: 10.1002/ajp.20675
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between zoo‐housed great apes and local wildlife

Abstract: Although there are published reports of wild chimpanzees, bonobos, and orangutans hunting and consuming vertebrate prey, data pertaining to captive apes remain sparse. In this survey-based study, we evaluate the prevalence and nature of interactions between captive great apes and various indigenous wildlife species that range into their enclosures in North America. Our hypotheses were threefold: (a) facilities housing chimpanzees will report the most frequent and most aggressive interactions with local wildlif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Chimpanzees rarely capture an animal without eating it, but this puzzling pattern occurs in both nature and captivity, mostly by youngsters [1][2][3][4][5][6] . At Bossou in Guinea, chimpanzees rarely hunt for meat; their home range presents few suitable prey 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Chimpanzees rarely capture an animal without eating it, but this puzzling pattern occurs in both nature and captivity, mostly by youngsters [1][2][3][4][5][6] . At Bossou in Guinea, chimpanzees rarely hunt for meat; their home range presents few suitable prey 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Data from zoos have shown that captive bonobos are more aggressive toward local wildlife than expected, and the rate of their aggressive interactions is almost the same as that of chimpanzees (Ross et al 2009). Ross et al (2009) reported that all facilities keeping captive bonobos have experienced the capturing of wildlife by bonobos.…”
Section: Discussionmentioning
confidence: 92%
“…Ross et al (2009) reported that all facilities keeping captive bonobos have experienced the capturing of wildlife by bonobos. The accumulation of reports on hunting or interspeciWc interaction in wild bonobos may lead to a novel understanding of the aggressive nature of bonobos toward sympatric animals including primates.…”
Section: Discussionmentioning
confidence: 98%
“…Most actors of chimpanzee side are mother and offspring, and all actor of guenon side is solitary male. Because adult chimpanzees tend to be aggressive to other species (Ross et al 2009), guenons probably avoid groups of chimpanzees, especially groups of adult male chimpanzees (but see Hosaka & Ihobe 2015). However, immature chimpanzees have a relatively small body size, and thus guenons may be able to approach non-adult chimpanzees without fear of lethal aggression.…”
Section: Discussionmentioning
confidence: 99%